Looking into media frames exploratory study on local MPOX reportage in the Philippines from August to December 2024 - Lesaca, Thony Rose F.
This exploratory study analyzed the media framing of MPOX articles in the online platforms of ABS-CBN News, GMA News, and News 5 during the disease’s re-emergence in 2024. De Vreese’s framing theory (2005) and White’s gatekeeping theory (1950) were integrated into a framework that guided the content analysis of 153 news articles published by the three mainstream media outlets from August to December 2024. Interviews with three mainstream health reporters were also conducted to give more context to the findings of the content analysis. The study revealed that ABS-CBN News, GMA News Online, and News 5 had predominant negatively-toned articles that utilized public health frames in reporting about MPOX. Disinformation factors such as the use of artificial intelligence (AI), stigmatization, and perceived COVID-19 sensitivity were also identified as themes of the MPOX re-emergence in 2024.